IMPACT OF THE COVID-19 INFECTION ON THE LIFE QUALITY (Zdravstveni glasnik, 2024)
Introduction: Due to the consequences of the COVID-19 pandemic, experts have expressed concern forpsychological functioning and well-being globally, with a particular reference to life quality disorder.Aim: To determine the connectin of recovery and the degree of life quality.Respondents and methods: A cross-sectional survey is carried out. The sample in the research consist ofpersons of both sexes at the age of 18, who have recovered from the infection, reviewing more than a yearsince the beginning of this research. The test survey was done by 384 respondents, which was carried outfrom October to December 2022. It was used a questionare survey, designed for research purpose, consistingof socio-demographich characteristics, characteristics of COVID-19 infection and consequences of COVID19 infection.Results: By the comparison of established frequencies of response, confirmations of agreement anddisagreement of the claims examinated is established that significantly higher percentage of respondentshave noticed, in their functioning after COVID-19 infection, the appearance of fatigue and musclesweakness (65,9%), significant hair loss (57,8) and higher level of symptoms of depression and anxiety(43,8%).Conclusion: The COVID-19 pandemic has markedly influenced life quality and has affected all aspects oflife and health.